2019
DOI: 10.3390/cancers11030376
|View full text |Cite
|
Sign up to set email alerts
|

Ion Channels: New Actors Playing in Chemotherapeutic Resistance

Abstract: In the battle against cancer cells, therapeutic modalities are drastically limited by intrinsic or acquired drug resistance. Resistance to therapy is not only common, but expected: if systemic agents used for cancer treatment are usually active at the beginning of therapy (i.e., 90% of primary breast cancers and 50% of metastases), about 30% of patients with early-stage breast cancer will have recurrent disease. Altered expression of ion channels is now considered as one of the hallmarks of cancer, and several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 182 publications
0
51
0
Order By: Relevance
“…Ion channels have important roles in regulating various cellular processes underlying animal development and tissue homeostasis. Altered levels of ion channel expression as well as their activity are often associated with aggressive phenotypes of cancers, such as proliferation, apoptosis, migration, and drug resistance [3,4,5,6]. Various types of ion channels have been suggested as prognostic markers and/or therapeutic targets in GC/SC [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ion channels have important roles in regulating various cellular processes underlying animal development and tissue homeostasis. Altered levels of ion channel expression as well as their activity are often associated with aggressive phenotypes of cancers, such as proliferation, apoptosis, migration, and drug resistance [3,4,5,6]. Various types of ion channels have been suggested as prognostic markers and/or therapeutic targets in GC/SC [7].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have shown a clear link between calcium channel expression and sensitivity to therapeutic drugs. Many calcium channels are involved in quimioresistance acquisition in a large variety of cancers [80]. To date, in addition to our group results, there are no studies about TTCCs and melanoma treatment resistance acquisition.…”
Section: T-type Calcium Channels and Braf Inhibitor Resistance In Melmentioning
confidence: 47%
“…observations have been made in prostate cancer where Orai3 overexpression is positively correlated with aggressive cancer phenotypes and poor clinical prognosis [137]. Furthermore, the expression profile of Orai channels has been associated with chemoresistance in many cancers [142]. For example, Orai1 expression is upregulated in cisplatin-resistant ovary carcinoma cells compared to their parental cells, and its pharmacological inhibition by 2-APB enhances cisplatininduced cell death in resistant cell lines [143].…”
Section: Trp-mediated Ca 2+ Transportmentioning
confidence: 99%